Hak Atas Privasi Anak: Isu Sepele Yang Mengancam Martabat Anak Usia Dini - Nur Rachmawati, Dian; Pinilih, Sekar; Imamah (PT Ininnawa Paramacitra Edukasi, 2025)
The development of digital technology in early childhood education offers both opportunities and threats to children’s rights to privacy and dignity. The phenomenon of sharenting and the publication of children’s data by early childhood education institutions reflect low levels of digital literacy and the absence of a strong personal data protection policy in Indonesia. This study aims to analyze violations of young children’s right to privacy from national and international legal perspectives, particularly Articles 16, 17, and 3 of the Convention on the Rights of the Child (CRC), as well as Islamic values concerning honor (hifzh al-‘ird). The study employs a normative juridical and descriptive-analytical approach, using data derived from legal documents, books, and scholarly articles published between 2021 and 2025. The findings indicate that privacy violations among children are caused by disparities in digital literacy among teachers, parents, and children, as well as the lack of ethical education guidelines. The results further highlight that digital ethics education at the early childhood level should be integrated into character education curricula so that children, teachers, and families collectively understand the boundaries of privacy and social responsibility in digital spaces. The study also emphasizes the importance of collaboration among the state, educational institutions, and society in formulating technology-based child protection regulations. Integrating legal principles, digital character education, and Islamic values is essential to achieve comprehensive and dignified child protection.